A new method for measuring the adhesion strength of rock-concrete specimens based on the calibration interface of the modified flat-joint model. (December 2022) - Li, Xiaojing; Lan, Lijie; Zhang, Jianguo; Tang, Jianhui; Lv, Mingying; Liu, Chengzhi; Han, Xuerui
Highlights: Study on the adhesion strength of rock-concrete interface by PFC 3D . Derive the interface stiffness equation combined interface mechanics. Modify the flat-joint model to simulate the interface of rock-concrete. The propagation process of interface plane crack is analyzed. The numerical model can accurately estimate the interface adhesion strength. Abstract: In tunnel engineering constructed by NATM, the adhesion strength between surrounding rock and lining is an important index to measure the safety of tunnel construction. However, the field measurement and laboratory test inevitably have the problem of low efficiency. In contrast, reasonable numerical simulation can be an alternative way to study rock-concrete adhesion strength. Therefore, in this paper, the influence factors of the adhesion strength of rock-concrete are studied by direct tensile laboratory test combined with particle flow code in three-dimension (PFC 3D ). The flat-joint model was used to reproduce the behavior of rock and concrete. The concept of effective elastic modulus of bi-material interface was introduced to derive the modified equation of interface normal stiffness. Then the modified flat-joint model was applied to PFC 3D based on the Fish language and the interface parameters were calibrated. Compared with the results of laboratory tests, it is found that this method can accurately simulate the adhesion strength between rock and concrete, which can also restore the post-peak response of laboratory tests. Therefore, more parameter studies are considered which show that: the mechanical properties of rock have little influence on the adhesion strength of composite specimens. However, the physical properties of rock, such as porosity, have great influence on that, which can be seen from the crack propagation mode at the interface of composite specimens. Sandstone cemented better with concrete will retain the rate sensitivity of rock and concrete materials to the greatest extent. When the experimental strain rate increases from 0.06 s −1 to 0.9 s −1, the adhesion strength of sandstone-concrete specimens increases by 50 %, while that of granite-concrete specimens hardly changes. The research results can be helpful to better understand the adhesion performance of rock-concrete interface and have certain engineering significance for tunnel construction supported by shotcrete.